Main changes in english students and teachers roles within virtual education - Martínez Vega, Kenny Diane
Certainly, virtual education also referred to as online, remote, and distance education is an old teaching modality around the globe. It originated back in the 1960s in The U.S. A correspondence-based course via postal service. Technology has come to change not only the way people work but also the way people learn. Nevertheless, nobody was completely prepared for the challenge that virtual education brought. Have teachers and students acquired or changed their roles, activities, or even their skills to face that education modality? Books and notebooks are now students and teachers’ computers, tablets, etc. Furthermore, the classroom is now a digital platform where people from anywhere join. Therefore, another key question arises, how do these evolving roles impact on methodologies applied to virtual environments? These are the underlying questions that this research work aims to address. Hence, the students of this specialization course, went over several technological resources to design and develop virtual classes. Besides that, students developed teaching content through virtual platforms so as to adequate methodologies to their current needs of virtual learners. All in all, the new skills and knowledge acquired during this lesson by the students of the specialty course was also attached to this work.